Data Analytics for business: AI-ML-PBI-SQL-R - Garn, Wolfgang (London Routledge, 2024)
We are drowning in data but are starved for knowledge. Data Analytics is the discipline of extracting actionable insights by structuring, processing, analysing and visualising data using methods and software tools. Hence, we gain knowledge by understanding the data. A roadmap to achieve this is encapsulated in the knowledge discovery in databases (KDD) process. Databases help us store data in a structured way. The structure query language (SQL) allows us to gain first insights about business opportunities.
Keywords: Economics; Finance; Business; Industry